Assessment of Marginal Fit and Accuracy of Crowns Fabricated Using CADCAM Milling and 3D Printing Technology - M.V. Sunil Kumar; Rajesh Kumar; Ravindher S. Saini; Rajesh Vyas; Saraswathi Bai; Sunil K. Vaddamanu (Journal of Pharmacy and Bioallied Sciences)
Background: This study evaluates the accuracy of marginal and internal fits of dental crowns fabricated using CAD/CAM milling and 3D printing technologies. The hypothesis posited significant differences between these techniques, confirmed by data showing notable disparities. Materials and Methods: Using the silicone replica technique, 44 points on each crown were measured, with seven crowns per method to ensure reliability. Results: Results indicated that 3D printing demonstrated superior precision, with the smallest discrepancies in occlusal, axial, and marginal gaps. While milling faced challenges such as material wastage and potential ceramic microfractures, it remained a viable option. Conclusion: The findings suggest that 3D printing could significantly improve crown quality and patient outcomes, despite higher upfront costs. Further research is necessary to validate these results and explore the long-term efficacy and cost-effectiveness of these techniques. This study underscores the clinical implications of choosing appropriate crown fabrication methods, highlighting the potential of advanced CAD/CAM technologies to enhance dental prosthetic manufacturing.